How to measure trends in the work environment—a workshop at the international NAM-NIVA Summer School 2007 - Burr, Hermann; Ploug, Niels (SJWEH Supplements, 2008)
The workshop aimed at improving the quality of surveillance data to make analyses such as trends in the work environment possible. It focused on interview-based measurements on a national level at several points in time. Issues and perspectives such as the organizational context of surveillance, social indicators, questionnaire design, and surveillance programs were presented. The impact of a political, administrative, and scientific context on surveillance was considered very important. Data on the work environment are also social indicators and are thus a supplement to economic indicators. It was agreed that a social indicator should be responsive to policy interventions but not subject to manipulation. The wording of interview questions should be unambiguous and precise. Finally, the Danish Work Environment Cohort Study was described. It was concluded that the surveillance community could benefit from agreed principles from the social indicator community; data quality affects data analyses; built-in cohorts make it possible to determine the predictive validity; and surveillance programs with representative data on the work environment and data on occupation make analyses of trends in the work environment possible.
Keywords: epidemiology; NAM; NAM-NIVA Summer School; NAM-NIVA Summer School 2007; NIVA; Nordic Conferences of the Work Environment; Nordic Institute for Advanced Training in Occupational Health; quality; surveillance; trend; validity; work environment; workshop